2014
DOI: 10.1177/1557988314555122
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sexual Function and Its Contributing Factors in Men With Spinal Cord Injury Using a Self-Administered Questionnaire

Abstract: Sexual activity is an important aspect of life in patients with spinal cord injury (SCI), rated as one of the top priorities for recovery of function. This study was conducted to establish an understanding of the severity of erectile dysfunction (ED), a major component of male sexual activity, and its correlates in patients with SCI in our community. In a crosssectional study, 37 male veterans with SCI admitted for regular follow-up at our center were recruited. Demographic and SCI-related descriptive informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 33 publications
(32 reference statements)
0
2
0
3
Order By: Relevance
“…For tetraplegic patients, this worry is secondary, because regaining the motor function is their priority, given the greater impairment of motricity and mobility they suffer. (2,(4)(5)(6) Sexual satisfaction is an important aspect of the life of people with spinal cord injury, and different treatment methods for sexual dysfunctions and adaptations in sex life must be considered to improve the quality of life of these people. (6,7) Healthcare professionals have the responsibility to promote sex education of people with spinal cord injury to reduce the impact of the condition on sexuality and the sexual function and improve the quality of life of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…For tetraplegic patients, this worry is secondary, because regaining the motor function is their priority, given the greater impairment of motricity and mobility they suffer. (2,(4)(5)(6) Sexual satisfaction is an important aspect of the life of people with spinal cord injury, and different treatment methods for sexual dysfunctions and adaptations in sex life must be considered to improve the quality of life of these people. (6,7) Healthcare professionals have the responsibility to promote sex education of people with spinal cord injury to reduce the impact of the condition on sexuality and the sexual function and improve the quality of life of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…People living with SCI can go beyond genital sex and promote their sexual motivation, capacities, and performance. Importantly, however, research findings have found that couples must receive sexual rehabilitation after SCI to maintain their partnership [48].…”
Section: Discussionmentioning
confidence: 99%
“…As amostras dos estudos foram heterogêneas em relação ao gênero dos indivíduos incluídos. A população mais prevalente foi de apenas homens 1,6,8,10,15,22 ou de homens e mulheres, sendo nesse caso a porcentagem de mulheres menor. 7,12,13,[16][17][18][19][20][21] Essa prevalência de homens pode ser decorrente da predominância masculina entre os indivíduos traumaticamente lesados e também pelo fato de que a disfunção sexual feminina pode ser considerada menos problemática para as mulheres do que para os homens, pois ainda existe a crença de que as mulheres possuem um papel passivo na relação sexual.…”
Section: Discussionunclassified
“…Alguns estudos 8,10,[12][13][14][15][16] incluíram instrumentos de avaliação de fatores não específicos da sexualidade, mas que estão intimamente relacionados a ela. Dentre os instrumentos, pode-se citar: EuroQol, General Health Questionnaire (GHQ-12), The Hospital Anxiety and Depression Scale (HADS), Rosenberg Self-Esteem Scale (RSES), Sickness Impact Profile (SIP), Mood Adjective Check List (MACL), Spinal Functional Ability Scale (S-FAS) e International SCI Basic QoL Data Set.…”
Section: Discussionunclassified
See 1 more Smart Citation